Motifs of Repetition of Fate and Return to the Past in Some of Sam Shepardâ€™s Plays - Starja, Anxhela (Mediterranean Journal of Social Sciences, 2012)
Sam Shepard once commented on what he deemed the notion of family and heredity: â€œWhat doesnâ€™t have to do with family?There isnâ€™t anything, you know what I mean? Even a love story has to do with family. Crime has to do with family. We all come out ofeach other everyone is born out of a mother and a father, and you go on to be a father. Itâ€™s an endless cycle.â€. Critics consider Curse ofthe Starving Class (1977) and Buried Child (1978) the ô€‚¿rst two parts of a â€œfamily trilogyâ€ completed by True West (1980), or the ô€‚¿rst twoplays in a quintet â€“ those three works plus Fool for Love (1983) and A Lie of the Mind (1985). True West and A Lie of the Mind areflooded with references to the past, as the characters eagerly attempt to fix familial and cultural history. The obsession with memoryleads to an awareness of erosion, perhaps a desire to forget, repress, ignore, deny or falsify the facts. However, in Shepardâ€™s work,nothing is further from the truth that all the characters feel in their unconsciousness and refuse uttering. The terms â€œhomecomingâ€ andâ€œheritageâ€ are bullets capable of crushing any preconceived notion of either. Upon closer inspection, legacy takes the form of addiction,disconnection, and displacement whereas homecomings provide shelter and entrapment, offering numberless opportunities to recover,dredge up, or scatter the ashes of the past.